2020
DOI: 10.1080/15384101.2020.1804222
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of Net1/Cdc14 by the Hog1 MAPK upon osmostress unravels a new mechanism regulating mitosis

Abstract: During evolution, cells have developed a plethora of mechanisms to optimize survival in a changing and unpredictable environment. In this regard, they have evolved networks that include environmental sensors, signaling transduction molecules and response mechanisms. Hog1 (yeast) and p38 (mammals) stress-activated protein kinases (SAPKs) are activated upon stress and they drive a full collection of cell adaptive responses aimed to maximize survival. SAPKs are extensively used to learn about the mechanisms throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 163 publications
0
4
0
Order By: Relevance
“…For full adaption to extracellular stimuli, Hog1 exerts several adaptive responses in the cell, including the regulation of cell cycle progression [ 44 , 45 ]. Consequently, we analyzed whether Hog1 was important in the mediation of cell-cycle delay upon copper exposure.…”
Section: Resultsmentioning
confidence: 99%
“…For full adaption to extracellular stimuli, Hog1 exerts several adaptive responses in the cell, including the regulation of cell cycle progression [ 44 , 45 ]. Consequently, we analyzed whether Hog1 was important in the mediation of cell-cycle delay upon copper exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Just as Hog1 modulates physiology via multiple mechanisms in response to stress, it also initiates cell cycle arrest by several methods: First, Hog1 delays the expression of cell phase-specific transcripts to prevent progression. Second, Hog1 directly phosphorylates cell cycle regulatory proteins to modulate their activity, thus preventing progression [ 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 ]. Thus, proper Hog1 activity to promote cell cycle arrest in response to stress is crucial for cell survival.…”
Section: Key Regulators That Govern Physiological Pathways Rewired Fo...mentioning
confidence: 99%
“…It was recently shown that activated Hog1 phosphorylates the core subunit of the RENT complex, Net1, at Thr62 and Ser385, and in that way alters its affinity for the dual-specificity phosphatase Cdc14 (Jimenez et al . 2020 ). The activity of Cdc14 is tightly regulated by its subcellular localization, and during most of the cell cycle Cdc14 is kept sequestered at the nucleolus by Net1.…”
Section: The Cell Cycle and Osmostressmentioning
confidence: 99%
“…The Hog1-dependent phosphorylation of Net1 makes the Net1-Cdc14 complex more resistant to modifications by CDK and leads to that Cdc14 is sequestered at the nucleolus and mitosis is delayed (Jimenez et al . 2020 ). Consequently, the phosphorylation-negative mutant of Net1 (Thr62Ala, Ser385Ala), that cannot be phosphorylated by Hog1, displays reduced viability upon osmostress.…”
Section: The Cell Cycle and Osmostressmentioning
confidence: 99%